Design and Fabrication of a Hybrid Battery with Lead Acid Battery and Supercapacitor - Prof. Mugdha Bhajekar; Prof. Sonali Mahajan; Mahesh Potdar; Swapnali Nigade; Shreyada Patil; Omkar Vallakati (International Journal of Engineering and Management Research, 2023)
The electricity plays very important role in today's world and Day by day the need of energy is increasing due to which the energy storing is becoming the need of today’s world. To solve this problem, we have to use the energy storing devices such as batteries, super capacitor etc. The batteries are the widely used device to store electrical energy but the costs of these batteries are increases as per its storing capacity.[1] To reduce this cost we are going to make the batteries which will be more affordable to the consumer and also we are going to increase the energy storing capacity of the batteries. Generally, the batteries consist of two electrodes one is positive and another one is negative and these electrodes are dipped in the electrolyte solution.[2] In this project we have made a super capacitor which is used as a second electrode of lead acid battery. We have connected this super capacitor in series with the negative electrode. Super capacitors have high energy storing capacity, due to addition of this super capacitor, the energy storing capacity of battery increases and also the life of battery increases.[3]